Interpretation Uncertainty of Consumer Life Insurance Offered by Selected Banks - Nowak, Katarzyna (Journal of Finance and Financial Law, 2021)
Bundled package of home loans and insurance are a natural phenomenon. Banks treat insurance as the primary security for the credit. For the consumer–borrower can help in financial difficulty. The purpose of insurance added to the loan is to reduce the risk of inability of borrowers to pay back their loans to banks and to ensure the safety of the insured or beneficiary of the insurance policy Therefore, insurance added to the loans should effectively protect borrowers. However, bundled package entails the risk of mismatching the insurance cover with the individual policy-holder insurance needs. Consumer–borrower may not be aware of the scope of insurance protection, which results from the insurance contract and general insurance terms and conditions. Therefore, in order to properly understand the offer of insurance, it becomes necessary to familiarize the borrower–the consumer with the general insurance conditions. However, as research shows, there is a big problem on the insurance sector with unintelligible insurance policy. The purpose of the article/hypothesis: The aim of the article is to compare and assess the scope of insurance cover based on the provisions of the general conditions of life insurance added to home loans by the two largest banks in Poland. Methodology: The article uses a comparative analysis of the scope of insurance cover on the based on provisions of the general conditions of insurance. The following categories have been selected from the general conditions of insurance: subject of insurance, definitions of events covered by the liability of the insurer, nature of benefits, amount of insurance and exclusions and limitations of liability. Results of the research: the analysis of the scope of insurance cover at selected banks in the article shows that selected categories from the general terms and conditions of insurance limit the potential level of insurance cover. After reviewing the general terms and conditions of insurance, consumer–borrower is not sure whether he will get help from the insurer when he needs it.